Malaria vivax en niños : recurrencias con dosis total estándar de primaquina administrada durante 3 frente a 7 días (2010)
ABSTRACT: Worldwide, the efficacy of cloroquine-primaquine for treating acute Plasmodium vivax malarious attacks has not been thoroughly evaluated. In Latin America such studies are scarce, and in Colombia, almost nonexisting. Objective: To assess the efficacy of two regimens for administration of primaquine in children aged less than 18 years. Methodology: A clinical, controlled, unmasked study was carried out, with randomized administration of two primaquine regimens, namely: 0.50 mg/kg/day for 7 days (0.50-7) vs. 1.17 mg/kg/day for 3 days (1.17-3). Results: A. Healing of the acute attack: efficacy was 100% in both groups. B. Prevention of recurrences during 120 days: recurrences occurred in 68.4% of children treated with the 1.17-3 regimen, and in 34.2% of those receiving the 0.5-7 one. Conclusions: 1. Proportion of recurrences during the 120 days follow-up was significantly lower (34.2%) in children receiving the 0.50-7 regimen than in those treated with the 1.17-3 one (68.4%). The length of administration of the same total dose of primaquine influenced its efficacy against recurrences: shorter periods of administration were associated with lesser efficacy.